Implementation of sustainable healthy diet in urban household consumption - Dhyani Swamilaksita Prita; Farida Baliwati Yayuk; Martianto Drajat; Briawan Dodik; Ahzaini Laili Nur (BIO Web of Conferences)
A sustainable healthy diet is one that is nutritionally adequate and healthy, safe, culturally acceptable, economically fair and affordable, and has little environmental impact. This definition adds human health to the social, economic, and environmental dimensions. This study examines the implementation of a sustainable healthy diet in urban households in terms of health, socioeconomic, and environment, where the indicators include food consumption (amount and type), the proportion of food expenditure, and food waste (grams/capita/day) generated. The methodology used in this study was a cross-sectional method, where data collection was carried out from November 2023 - January 2024 in urban housewives. The results showed that the average diversity of consumption was quite good, with an average of 69.9 (>42), but only <20% had normal energy consumption levels, and <50% had normal protein consumption levels. The proportion of food expenditure of the population averaged >60% (70.5%) of total income, while household food waste generated amounted to 319.2 grams/day or equivalent to 79.8 g/cap/day with cereals and vegetables as the highest type of food waste. Therefore, it can be concluded that in this study, sustainable healthy eating patterns in urban households were not achieved. Education is needed to increase awareness of balanced nutrition consumption so that the quality of consumption increases along with the reduction of food waste.